A nuanced approach for assessing OPV materials for large scale applications. Issue 2 (12th December 2019) - Al-Ahmad, Alaa Y.; Almayhi, Furqan; Al-Mudhaffer, Mohammed F.; Griffith, Matthew J.; Liu, Wenqing; Li, Shuixing; Sivunova, Kamilla; Elkington, Daniel; Cooling, Nathan A.; Feron, Krishna; Shi, Minmin; Belcher, Warwick; et al.
Abstract : A systematic approach for assessing organic photovoltaic (OPV) materials for large scale production based on the efficiency, lifetime and material cost has been developed. A Ω of 2.55 results in the following maximum material cost. Abstract : A systematic approach for assessing organic photovoltaic (OPV) materials for large scale production based on the efficiency, lifetime and cost has been developed. These parameters have been combined to establish a figure of merit, Ω, which determines the suitability of OPV materials for real-world large-scale implementation. As a case study, small scale device efficiency optimization, lifetime measurements and cost analysis of the P3HT:SF(DPPB)4, P3HT:ICxA and P3HT:PCBM systems was undertaken. The figure of merit developed through these case studies is also shown to be suitable for broader assessment of all materials incorporated into manufacturing of OPV technology. Despite the relatively large differences in optimized small scale device efficiency P3HT:PCBM was, with an Ω value of 8.3 per m 2 per %, calculated as the most cost effective material system tested herein. This work demonstrates that small scale device efficiency alone is not a good proxy for the suitability of OPV material systems for large scale manufacturing and that the cost effectiveness figure of merit provides the more nuanced approach that is required.